Erecting Malaysia's 'maritime fence' over the straits of Malacca and Singapore - Mohd Rusli, Mohd Hazmi; Hamid, Abdul Ghafur@Khin Maung Sein; Wan Talaat, Wan Izatul Asma; Mustafa, Maizatun (The Secretariat, Asian-African Legal Consultative Organization, New Delhi, 2014)
Malaysia shares the Straits of Malacca and Singapore with Indonesia, Singapore and briefly with Thailand. The Anglo-Dutch Treaty of 1824 has divided the Straits of Malacca and Singapore into two spheres of dominions, which later on become the basis of modern territories of Malaysia, Indonesia and Singapore. Since independence, Malaysia has been working closely with Thailand, Indonesia and Singapore to properly demarcate maritime boundary lines in the Straits of Malacca and Singapore. Nevertheless, there are still unresolved issues between these littoral States in demarcating boundaries in these straits. This may create difficulties particularly when the issues of exerting sovereignty or exercising sovereign rights come into picture. This article concludes that Malaysia should continue to work closely with its immediate neighbors particularly Singapore and Indonesia in resolving these unsettled maritime boundary issues in the Straits of Malacca and Singapore.